Trust in Scholarly Communications and Infrastructure: Indigenous Data Sovereignty - Ruckstuhl, Katharina (Frontiers in Research Metrics and Analytics, 2022)
Many Indigenous people have a deep mistrust of research, with some describing research as one of the ‘dirtiest’ words in Indigenous language. The histories and experiences behind such mistrust are long and painful. Given what has been perceived as Indigenous objectification at the hands of largely Anglo-European others for research from which they fail to benefit, many communities now refuse research unless it is undertaken under certain, Indigenous-defined circumstances. Such refusal is a move away from others’ purposes and a move towards autonomy and self-determination. For some, this is a statement of sovereignty and it applies to all areas of endeavour, including the new frontiers of research and the structures that support them, such as datification of knowledge. This article examines data sovereignty from the perspective of Indigenous peoples. While data sovereignty has become a ubiquitous concern, Indigenous data sovereignty arises from contexts specific to Indigenous peoples. The focus of this article is to provide a brief overview of recent data sovereignty developments, along with the context that lies behind these activities. Through this examination, implications for trust in scholarly communications will be discussed.